25,41-3×(1,2+0,7)
11,18:[9,4-2×(1,2-0,8)]
Răspunsuri la întrebare
Răspuns de
65
Explicație pas cu pas:
Bună!
25,41 - 3 × (1,2 + 0,7) =
25,41 - 3 × 1,9 =
25,41 - 5,7 =
19,71
11,18 : [9,4 - 2 × (1,2 - 0,8)] =
11,18 : (9,4 - 2 × 0,4) =
11,18 : (9,4 - 0,8) =
11,18 : 8,6 =
1,30
==pav38==
andreiboss1739:
ms
Alte întrebări interesante
Biologie,
8 ani în urmă
Biologie,
8 ani în urmă
Limba română,
8 ani în urmă
Engleza,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă